Persiapan Fisik Terhadap Efek Pasca Vaksinasi COVID-19 pada Tenaga Kesehatan - Haerianti, Masyita; yunding, junaedi (Journal of Health Education and Literacy, 2023)
Coronavirus disease 2019 (COVID-19) is a world health problem that causes various threats to people around the world. One of the efforts to overcome COVID-19 is by administering a vaccine. The first target of vaccine administration is health workers as the frontline in fighting COVID-19 and as populations that are very vulnerable to exposure the COVID-19. Health workers need to make physical preparations before vaccination so that the immune system remains keep strong and body can form immunity optimally against the Coronavirus and felt side effects after the vaccine are minimal. This type of research is descriptive analytic with cross-sectional design with a total sample of 108 respondents. The instruments used in this study consisted of three questionnaires there are demographic data questionnaire, physical preparation questionnaire and post-vaccination effect questionnaire. Data analysis consisted of univariate analysis and bivariate analysis using the chi-square test (α) <0.05. The majority of respondents did physical preparation, did not feel the side effects after the vaccine and there was no relationship between physical preparation and side effects after the vaccine so further research was needed to regarding other factors that possibility affect such as gender, dosage, time of administration and health conditions.